2019
DOI: 10.1038/s42003-019-0420-8
|View full text |Cite
|
Sign up to set email alerts
|

ALK2 inhibitors display beneficial effects in preclinical models of ACVR1 mutant diffuse intrinsic pontine glioma

Abstract: Diffuse intrinsic pontine glioma (DIPG) is a lethal childhood brainstem tumour, with a quarter of patients harbouring somatic mutations in ACVR1 , encoding the serine/threonine kinase ALK2. Despite being an amenable drug target, little has been done to-date to systematically evaluate the role of ACVR1 in DIPG, nor to screen currently available inhibitors in patient-derived tumour models. Here we show the dependence of DIPG cells on the mutant receptor, and the prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(143 citation statements)
references
References 44 publications
2
140
0
1
Order By: Relevance
“…Recent genetic studies have shown that up to 90% of DMGs have H3K27M mutations in H3F3A encoding histone H3.3 or (Figure 5) (10,36,39). We established a DIPG cell line harboring the H3.1 H3K27M and ACVR1 G328E mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genetic studies have shown that up to 90% of DMGs have H3K27M mutations in H3F3A encoding histone H3.3 or (Figure 5) (10,36,39). We established a DIPG cell line harboring the H3.1 H3K27M and ACVR1 G328E mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the present research suggests that BMP pathway can be activated in ACVR1-wildtype DMGs as well. Development of multiple DMG cell lines which harbor ACVR1 mutation is necessary for further research (39).…”
Section: Future Directionsmentioning
confidence: 99%
“…66) In an orthotopic xenograft mouse model bearing the H3K27M mutation, and in ACVR1 R206H mutant HSJDDIPG-007 cells, both compounds significantly extended survival compared with vehicle controls. 66) Despite these several potent ALK2 kinase inhibitors in development, none of these compounds is currently in clinical trials. However, BLU-782 was reported as a new scaffold ALK2 inhibitor, 67) which is currently in a phase II.…”
Section: Small-molecule Alk2 Inhibitorsmentioning
confidence: 94%
“…65) LDN-193189 and LDN-214117 exhibit oral bioavailability and were well-tolerated, with good brain penetration at potentially active concentrations. 66) In an orthotopic xenograft mouse model bearing the H3K27M mutation, and in ACVR1 R206H mutant HSJDDIPG-007 cells, both compounds significantly extended survival compared with vehicle controls. 66) Despite these several potent ALK2 kinase inhibitors in development, none of these compounds is currently in clinical trials.…”
Section: Small-molecule Alk2 Inhibitorsmentioning
confidence: 99%
“…The World Health Organization 2016 classi cation of central nervous system tumors describes 80% of DIPG tumors as having a histone mutation, H3 K27M mutant, which is associated with worse clinical outcome (4). ACVR1 mutations are the second most common mutation in DIPG, with approximately 25% of cases harboring this mutation (5). These mutations contribute to the aggressive biology and poor treatment response.…”
Section: Introductionmentioning
confidence: 99%